Rice-fallow management in eastern India: Challenges and opportunities for enhancing system productivity and profitability - Mohapatra, Bidhan K. (Agricultural Economics and Social Science Research Association, 2022)
Vast fallows in the rabi/dry season are an issue of serious concern in the agricultural production system of Odisha and other parts of eastern India. With a rainfed rice-based mono-cropping system, resource-poor and small and marginal farmers of eastern India are forced to dwell in the vicious circle of poverty. Recently, the issue of rice-fallow is among the top agendas for the policymakers, and so public investment is happening. However, ad hoc investments in fallow intensification do not yield sustainable and satisfactory results as it is a very complex and multi-dimensional problem (biotic, abiotic, policy, and socio-economic) requiring attention at various levels of intervention. With this backdrop, based on secondary data and information and the review of literature, this paper discusses the key issues and challenges in rice-fallow development and recommends some strategic interventions needed for converting those fallow lands into croplands, particularly in rabi season. Also, the paper studies ongoing programs/schemes of central and state governments related to fallow management, keeping in view that research on fallow management must go in parallel with ongoing programs/schemes. Authors recommend that partners in a collaborative approach; should assess pathways of sequencing investment and intervention to catalyze the intensification of rabi fallows. If conceivable and low-to-medium risk pathways are identified, and associated convening and catalytic roles are defined for partners; policy dialogue and execution plan will not be an issue as all the local governments and agencies already understand the need for fallow management. This paper will be helpful for planners, policymakers, and development stakeholders while framing the policies, designing programs, setting implementation strategies, monitoring systems, critically analyzing potentially who can invest and where, etc., for a sustainable and environment-friendly agricultural system for poverty reduction, and food and nutritional security.